Pendidikan Kesehatan Tentang Pencegahan Keguguran (Miskram) Pada Ibu Hamil Melalui Deteksi Dini Faktor Risiko - Susanti Susanti; Zumrotul Ula; Yulis Tinta; Bayu Larasati Wulandari; Rezqiqah Aulia Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Miscarriage is one of the complications of pregnancy that still occurs frequently and can cause physical and psychological effects on mothers. Miscarriage prevention needs to be carried out by increasing pregnant women's knowledge about risk factors and the importance of early detection. This community service activity aims to increase pregnant women's knowledge about miscarriage prevention through health education and early detection of risk factors. The implementation methods include health counseling, interactive discussions, and basic examinations such as blood pressure, hemoglobin levels, and obstetric history. Evaluation is carried out using pre-tests and post-tests to measure the increase in participants' knowledge. The results of the activity show an 85% increase in knowledge, as well as an increase in pregnant women's awareness of the importance of regular antenatal checkups. This activity is expected to contribute to reducing the incidence of miscarriage by increasing pregnant women's understanding and awareness of risk factors that can be prevented early on.